2018
DOI: 10.1002/bbb.1930
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing economic value in multifunctional buffers in the lower Mississippi river basin

Abstract: Integrating conservation practices with bioenergy has been recommended as a promising strategy to improve bioeconomy and water quality but the literature on the economics of this strategy is limited. This study evaluated the value proposition of reducing nutrient loss from cropland by implementing switchgrass riparian buffers in the Lower Mississippi River Basin (LMRB). Nutrient loss was simulated by using the Soil and Water Assessment Tool. The value proposition of nutrient abatement was quantified by estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Our results demonstrate that the farmers’ benefit from aboveground products alone from an ABL does not exceed that of row crops when the price of switchgrass ranges from $20 to $80 per dry short ton. However, similar to Xu, Wu, and Ha () and Werling et al (), our study also finds that the relative value of bioenergy crops could be increased by incorporating ecosystem services into the equation.…”
Section: Discussionsupporting
confidence: 88%
“…Our results demonstrate that the farmers’ benefit from aboveground products alone from an ABL does not exceed that of row crops when the price of switchgrass ranges from $20 to $80 per dry short ton. However, similar to Xu, Wu, and Ha () and Werling et al (), our study also finds that the relative value of bioenergy crops could be increased by incorporating ecosystem services into the equation.…”
Section: Discussionsupporting
confidence: 88%
“…Landscape-management approaches, such as integration of cellulosic biomass production with agricultural conservation practices (riparian buffers, constructed wetlands, and bioreactors), have shown good potential to reduce nutrients lost through surface runoff [8]. Similarly, Xu et al (2019) [9] found that growing switchgrass as riparian buffers along cropland can effectively intercept and recycle nutrient runoff from cropland. They also simulated nutrient load reductions through the Soil and Water Assessment Tool (SWAT) model.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased quantity may result in reduced crop production failing to feed the projected population of the world, while the incremental nutrient application will pollute the surroundings. Sustainable agricultural production thus necessitates supplementation of those nutrients either through natural processes (nitrogen fixation) or application through animal by-products or mineral fertilizers to crop fields [7][8][9][10][11][12]. Undesirable wastes are useful tools if managed properly instead of allowing them to contaminate soil, air, and water resources, which create a hazardous environment.…”
Section: Introductionmentioning
confidence: 99%
“…The high cost for restoring LO should not halt or delay restoration progress. To the contrary, state agencies should incentivize innovative practices to decrease/offset the cost of local and regional efforts to remove TP from surface waters, e.g., bioenergy production and novel landscape management [78][79][80], without delaying the immediate implementation of TP removal strategies delineated above. Finding knowledge gaps and incentivizing research and development in this area is critical to surpass the current level of treatment and lower capital and operational costs.…”
Section: Current State Action Plan and The Present Study Implicationsmentioning
confidence: 99%